Visual analogies in anatomic and clinical pathology - Kipersztok,Lisa; Masukume,Gwinyai; Lakhtakia,Ritu; Cohen,Michael B (PeerJ Preprints, 2016)
Visual medical analogies have been utilized by multiple medical disciplines for decades. Despite misgivings that some might have about such analogies, they act as excellent learning aids and will undoubtedly remain useful for decades to come. The microscope from about the seventeenth century onwards revolutionized medicine and cellular biology. In this article, we specifically consider in a pictorial essay culinary medical analogies as they pertain to the microscopic world, a gap in the literature on visual medical analogies.
Keywords: Microscope; pathology; metaphor; analogy; food